Application of native microbial inocula to the soil: effect in maize seedlings growth - Mendoza Sánchez, Saúl; Zepeda Hernández, Andrés; Campeche Calixto, Erendira Gabriela; Payán Zelaya, Fidel Adolfo (REVISTA TERRA LATINOAMERICANA, 2017)
The release of nutrients from decomposing plant residues is important to obtaining adequate crop nutrition especially in agroforestry systems. Some authors have pointed out the possibility of using microbial inocula to accelerate both residue decomposition and crop growth. In order to evaluate the response of maize (Zea mays) to application of liquid microbial inoculum on Erytrhina americana residues in the soil, an experiment was conducted in semi-controlled conditions. Maize was planted in pots filled with soil treated with microbial inocula from six different locations. Indicators of maize plant response were leaf area, biomass, and seedling height; CO2 production of soil in pots was also measured. The results showed that leaf area, biomass and CO2 production responded positively to the addition of foliage of E. americana. However, only microbial nutrient inocula from two locations caused significant differences in the variables evaluated, and none was superior to the results obtained with the control, which contained soil with residue addition but without microbial inoculants. The results indicate the need for further research on dose and frequency of application and they also highlight the usefulness of the method used to find differences in the impact of different inocula.